Optimality Conditions for a Nonsmooth Semivectorial Bilevel Optimization Problem. (17th February 2021) - Dempe, S.; Gadhi, N.; El Idrissi, M.
Abstract: In this paper, we are concerned with a nonsmooth semivectorial bilevel optimization problem ( P ). Using a scalarization technique, we transform the lower-level problem into several scalar optimization problems ( P z x s ) . We give necessary optimality condition in terms of the limiting subdifferentials and the limiting normal cones. Completely detailed first-order necessary optimality conditions are then derived in the special case where all functions are strictly differentiable.